2018
DOI: 10.5152/turkjsurg.2017.3795
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of abdominal gunshot injuries: Is it safe in all cases?

Abstract: Objective: In line with advances in diagnostic methods and expectation of a decrease in the number of negative laparotomies, selective non-operative management of abdominal gunshot wounds has been increasingly used over the last three decades. We aim to detect the possibility of treatment without surgery and present our experience in selected cases referred from Syria to a hospital at the Turkish-Syrian border. Material and Methods:Between February 2012 and June 2014, patients admitted with abdominal gunshot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 papers which documented the site of injury, only three were not specific to the injured anatomical region, allowed subcategorisation according to the AIS regions and were not case studies 12 16 27. Eighteen papers were site specific 10 13 18–22 24–26 28 29 33 38 39 42 44 46. Four could not be categorised in relation to the AIS 14 31 43 45.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of injury parameters, 49% of the population presented with a solid organ injury, and 61% presented with a bowel injury. The overall median ISS was 18 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and the median abdomendAIS was 3 (1-4). Most patients were transferred to level I ACS-verified trauma center (59%) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] The NOM of an AGW in select patients reduces the potential of postoperative complications, morbidity, and mortality associated with negative laparotomies. 20 A recently published Western Trauma Association critical decisions algorithm tackles the evaluation and management of AGWs. It recommends that patients selected for NOM should be awake, alert, and have a reliable abdominal examination that can be followed with serial examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation